Hubungan Kepatuhan Mengkonsumsi Obat Antidiabetik Oral dengan Kendali Gula Darah pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Mamajang - Wibowo, Suchika Aisyah; Nurmadilla, Nesyana; Dahliah, Dahliah; Iskandar, Darariani; Hamzah, Pratiwi Natsir (Syifa'Medika, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease that requires good management, including blood sugar control through adherence to oral antidiabetic drugs. This study aimed to analyze the relationship between medication adherence and blood sugar control in T2DM patients at Mamajang Community Health Center, February 2025. The method used was observational analytics with a cross-sectional approach. The research subjects were 57 T2DM patients who met the inclusion and exclusion criteria. Data were analyzed using univariate and bivariate analysis to test the relationship between medication adherence and blood sugar control. The results showed that adherence to treatment was significantly associated with HbA1c values (p = 0.042), but there was no significant relationship with fasting blood glucose levels (p = 0.360). This study concluded that although medication adherence affects HbA1c control, other factors such as diet, physical activity, and stress also play a role in blood sugar control. A more holistic approach to type 2 diabetes mellitus management is needed to improve optimal blood sugar management.